Dough flattening machine increase the performance of the onion chips artisan - Anizar, Anizar; Yahya, Idhar; Torong, Zainul Bahri (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2020)
Onion chips are foods made from a dough of flour, water and other ingredients that can be easily found in various places, but are generally made manually. Dough making is an activity that requires the longest time and greatly determines the quality of the resulting onion chips. Crafters need a long time, great effort and complaints of pain in several parts of the body due to this activity. This service activity provides a dough sheeting tool to facilitate the work of craftsmen and reduce activity time. The quality of the onion chips produced is getting better and craftsmen are also free from complaints of muscle pain.